Kinetic Study of Reduction of N-[4-[Bis[4-dimethylamino)-phenyl]-methylene]-2,5-cyclohexadiene-1-ylidene]-methanaminium Chloride with Iodide in Aqueous Ethanol System - Maria Ashfaq (Science Faculty of Chiang Mai University, 2019)
The kinetics of reduction of N-[4-[Bis[4-dimethylamino)-phenyl]-methylene]-2,5-cyclohexadiene-1-ylidene]-methanaminium chloride (methyl violet) with potassium iodide was studied in ethanol-water solvent spectrophotometrically at 579 nm. The reduction of methyl violet was studied at different concentrations of potassium iodide ranging from 0.1-0.5 mol.dm-3 in 10-30% ethanol-water system at pH 4.99 and 6.0. The rate of the reaction was studied at various temperature ranges from 298-318 K. The rate of the reaction was also influenced by medium and found to be faster as the polarity of the medium was lowered. The kinetic analysis show reduction of methyl violet with iodide is pseudo first order as first order with respect to potassium iodide and found independent of methyl violet concentration. Effect of temperature on the rate constant were analysed by Arrhenius relation used to calculate activation energy () from reduction reaction. The activation parameters such as enthalpy change of activation (ΔH*), entropy change of activation (ΔS*) and Gibbs free energy change of activation (ΔG*) were also evaluated.